Functional Characterization of a Missing Branch Component in Haematococcus pluvialis for Control of Algal Carotenoid Biosynthesis - Lao, Yong M.; Jin, Hui; Zhou, Jin; Zhang, Huai J.; Cai, Zhong H. (Frontiers in Plant Science, 2017)
Cyclization of acyclic lycopene by cyclases marks an important regulatory point in carotenoid biosynthesis. Though some algal lycopene epsilon cyclases (LCYEs) have been predicted computationally, very few have been functionally identified. Little is known about the regulation mechanisms of algal LCYEs. Recent comparative genomic analysis suggested that Haematococcus pluvialis contained only the β type cyclase (HpLCYB). However, in this study, carotenoid profiling found trace α-carotene in the salt-treated cells, indicating the in vivo activity of HpLCYE, a missing component for α-branch carotenoids. Thus, genes coding for HpLCYB and HpLCYE were isolated and functionally complemented in Escherichia coli. Substrate specificity assays revealed an exclusive cyclization order of HpLCYE to HpLCYB for the biosynthesis of heterocyclic carotenoids. Expression pattern studies and bioinformatic analysis of promoter regions showed that both cyclases were differentially regulated by the regulatory cis-acting elements in promoters to correlate with primary and secondary carotenoid biosynthesis under environmental stresses. Characterization of the branch components in algal carotenoid biosynthesis revealed a mechanism for control of metabolic flux into α- and β-branch by the competition and cooperation between HpLCYE and HpLCYB; and supplied a promising route for molecular breeding of cyclic carotenoid biosynthesis.